TDoA localization-refused area analysis and node placement strategy research - Yue ZHAO; Zan LI; Bing LI; Benjian HAO (Tongxin xuebao)
Regarding the Cramer-Rao lower bound (CRLB) as a localization accuracy metric, the sufficient conditions of the LRA in the time difference of arrival (TDoA)-based localization scenario were discussed and the influence of different factors on the LRA were analyzed.Furthermore, the node placement problem for wireless sensor network (WSN) was investigated by formulating an optimization problem with the objective as average CRLB, which was solved by a genetic algorithm based on LRA pre-judgment.Simulation validates the properties of the CRLB in a single-source scenario and verifies the sufficient condition and the spatial range of the LRA.The simulation also shows that the localization accuracy determined by the proposed algorithm is improved by 33.92% higher than the uniform angle array placement scheme, 13.74% compared to the regional vertex placement scheme, and 9.65% compared to the direct genetic algorithm.